Bi-specific T-cell engagers (BiTEs) in prostate cancer and strategies to enhance development: hope for a BiTE-r future - Lampe, Harriet; Tam, Laura; Hansen, Aaron R. (Frontiers in Pharmacology, 2024)
Metastatic castrate resistant prostate cancer (mCRPC) continues to have poor survival rates due to limited treatment options. Bi-specific T cell engagers (BiTEs) are a promising class of novel immunotherapies with demonstrated success in haematological malignancies and melanoma. BiTEs developed for tumour associated antigens in prostate cancer have entered clinical testing. These trials have been hampered by high rates of treatment related adverse events, minimal or transient anti-tumour efficacy and generation of high titres of anti-drug antibodies. This paper aims to analyse the challenges faced by the different BiTE therapy constructs and the mCRPC tumour microenvironment that result in therapeutic resistance and identify possible strategies to overcome these issues.